Staging identifies non-CNS malignancies in a large cohort with newly diagnosed lymphomatous brain lesions. Issue 9 (29th July 2019) - Malani, Rachna; Bhatia, Ankush; Wolfe, Julia; Grommes, Christian
Abstract: Lymphomatous brain lesions can represent primary central nervous system (CNS) lymphoma or secondary involvement as part of systemic disease (SCNSL). In this study, we characterize staging evaluations in a large patient cohort with newly-diagnosed brain lymphomas, to determine the frequency of SCNSL and secondary malignancies. This retrospective review includes 262 patients with newly-diagnosed lymphomatous CNS lesions evaluated at Memorial Sloan Kettering Cancer Center between 2006 and 2018. Staging procedures included PET scans in 180 (69%) patients, CT scans of chest/abdomen/pelvis (CAP) in 195 (74%) and bone marrow biopsies (BMB) in 177 (68%). PET scans were reported as abnormal in 34 of 180 (19%), CT in 50 of 195 (26%) and BMB in 15 of 177 (8.5%). A total of 24 non-CNS malignancies were identified (11.8%; 19 systemic lymphomas and 5 secondary malignancies). Thus, in patients with new lymphomatous brain lesions, performing initial systemic staging procedures can identify systemic lymphoma and additional malignancies, highlighting the importance of staging evaluations, in particular PET and BMB.